2019
DOI: 10.1007/s10584-018-2352-6
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of nineteenth century drought in southern Africa in different historical source types

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 38 publications
0
20
0
2
Order By: Relevance
“…Brázdil et al (2013) reconstructed drought in the Czech Lands from 1090 to 2012, also using instrumental data and documentary evidence. Nash et al (2019) identified drought events in southeast Africa including newspapers, colonial and missionary materials.…”
Section: Introductionmentioning
confidence: 99%
“…Brázdil et al (2013) reconstructed drought in the Czech Lands from 1090 to 2012, also using instrumental data and documentary evidence. Nash et al (2019) identified drought events in southeast Africa including newspapers, colonial and missionary materials.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, they correspond to today's drought definitions and classifications. The descriptions of impacts and consequences and the derived pathways of historical events are in most cases comparable to recent events (Erfurt et al, 2019;Blauhut et al, 2016;Glaser et al, 2016Glaser et al, , 2017Glaser et al, , 2018Brazdil et al, 2016or Nash et al, 2019. Therefore, a parallelization is possible.…”
Section: Discussionmentioning
confidence: 99%
“…A precipitation deficit is followed by a specific pathway. It first appears on the agricultural, then the hydrological and finally the socio-economic level -a development reflected by modern drought definitions (Nash et al, 2019;Erfurt et al, 2019). These time-and intensity-related chains of effects can be derived from the historical sources as characteristic pathways.…”
Section: Derivation Of Historical Pathways and Drought Categories Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Glaser et al (2017) have done the same for Central Europe, Brázdil et al (2019) for Northern Europe, and Pfister (2011) for Western Europe. To highlight only a few regions, Nash et al (2019) explore the relationship between society and natural risk in southern Africa, Barriendos and Rodrigo (2006) for the Iberian Peninsula, and Endfield (2007) for colonial Mexico. Some works have explored the possibility of establishing quantitative methodologies through contextual analysis (Gil-Guirado et al, 2016, 2019Glaser and Khale, 2020;Prieto and García Herrera, 2009;Diez-Herrero, 2020) with optimal results being obtained for regions with a common history and culture.…”
Section: Introductionmentioning
confidence: 99%